Whole-Brain Mapping of the Inputs and Outputs of the Medial Part of the Olfactory Tubercle - Zhang, Zhijian; Zhang, Hongruo; Wen, Pengjie; Zhu, Xutao; Wang, Li; Liu, Qing; Wang, Jie; He, Xiaobin; Wang, Huadong; Xu, Fuqiang (Frontiers in Neural Circuits, 2017)
The medial part of the olfactory tubercle (OT) is a brain structure located at the interface of the reward and olfactory system. It is closely related to pheromone-rewards, natural reinforcement, addiction and many other behaviors. However, the structure of the anatomic circuitry of the medial part of the OT is still unclear. In the present study, the medial part of the OT was found to be highly connected with a wide range of brain areas with the help of the pseudorabies virus (PRV) tracing tool. In order to further investigate the detailed connections for specific neurons, another tracing tool - rabies virus (RV) was utilized for D1R-cre and D2R-cre mice. The D1R and D2R neurons in the medial part of the OT were both preferentially innervated by the olfactory areas, especially the piriform cortex (Piri), and both had similar direct input patterns. With the help of the adeno-associated virus (AAV) labeling, it was found that the two subpopulations of neurons primarily innervate with the reward related brain regions, with slightly less axons projecting to the olfactory areas. Thus, the whole-brain input and output circuitry structures for specific types of neurons in the medial part of the OT were systematically investigated, and the results revealed many unique connecting features. This work could provide new insights for further study into the physiological functions of the medial part of the OT.